2022
DOI: 10.3389/fgene.2022.920689
|View full text |Cite
|
Sign up to set email alerts
|

Partial Least Squares Enhances Genomic Prediction of New Environments

Abstract: In plant breeding, the need to improve the prediction of future seasons or new locations and/or environments, also denoted as “leave one environment out,” is of paramount importance to increase the genetic gain in breeding programs and contribute to food and nutrition security worldwide. Genomic selection (GS) has the potential to increase the accuracy of future seasons or new locations because it is a predictive methodology. However, most statistical machine learning methods used for the task of predicting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…For example, Vargas et al (1998) , Vargas et al (1999) and Crossa et al (1999) used this methodology for interpreting genotype by environment interaction in maize and wheat. For prediction in GS, this methodology has been used by Monteverde et al (2019) , Colombani et al (2012) and by Montesinos-López et al (2022a) for UT predictions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Vargas et al (1998) , Vargas et al (1999) and Crossa et al (1999) used this methodology for interpreting genotype by environment interaction in maize and wheat. For prediction in GS, this methodology has been used by Monteverde et al (2019) , Colombani et al (2012) and by Montesinos-López et al (2022a) for UT predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-trait models under artificial deep neural networks have even been explored in genomic selection ( Montesinos-López et al, 2018 ; 2019c ). Recently, Montesinos-López et al (2022a) explored the use of the partial least square (PLS) regression methodology for the prediction of one full environment of a single trait. The authors’ benchmarked the performance of the PLS for predicting a UT with the Bayesian Genomic Best Linear Unbiased Predictor (GBLUP) method, and in all data sets the UT-PLS method outperformed the UT-GBLUP method by margins between 0% and 228.28% across traits, environments and types of predictors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Montesinos-López et al [ 35 ] investigated the partial least square (PLS) regression methodology for the prediction of one full environment of a single trait (ST) and compared its prediction performance with that of the GBLUP method. In all datasets, the ST-PLS method outperformed the ST-GBLUP method by margins between 0% and 228.28% across traits, environments, and types of predictors.…”
Section: Discussionmentioning
confidence: 99%
“…However, because we only reported the prediction performance across traits, other details could not be fully observed in the provided tables and figures. Furthermore, under the implemented sevenfold CV, we observed that in general, the MT-PLS model achieved slightly worse performance than MT-GBLUP and MT random forest models; however, this finding cannot be extrapolated to all types of cross-validation strategies because evidence suggests that when the goal is to predict a complete environment (or year), the ST-PLS and MT-PLS models outperform the ST-GBLUP and MT-GBLUP models by considerable margins [ 34 , 35 ], which can be attributed, in part, to the fact that the ST and MT-PLS models first involve a variable selection process during which a considerable amount noise is discarded, and at the end, the training process applied with a latent variable of inputs.…”
Section: Discussionmentioning
confidence: 99%